2023
DOI: 10.2166/wst.2023.127
|View full text |Cite
|
Sign up to set email alerts
|

Cr(VI) anion-imprinted polymer synthesized on mesoporous silicon via synergistic action of bifunctional monomers for precise identification and separation of Cr(VI) from aqueous solution by fixed-bed adsorption

Abstract: The novel Cr(VI) anion-imprinted polymer(Cr(VI)-IIP) was prepared by a surface imprinting technique with bifunctional monomers pre-assembly system based on mesoporous silicon (SBA-15). The synthesized Cr(VI)-IIP was characterized by Fourier transmission infrared spectra (FT-IR), EDS, scanning electron microscope (SEM), transmission electron microscope (TEM), X-ray powder diffractometer, N2 adsorption–desorption and thermogravimetric analysis (TGA), proving to be with a highly ordered mesoporous structure, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Under the optimal conditions, Cr(III) was absorbed quantitatively, but Cr(VI) was not retained. A novel Cr(VI)-IIP was synthesized on the surface of mesoporous silicon (SBA-15) using MAA and 4-VP as bifunctional monomers and Cr(VI) anion as template ion by surface thermal initiation imprinting technique [ 127 ]. Cr(VI)-IIP prepared possesses a strong selective adsorption ability for Cr(VI) in the presence of competing ions such as Cr(III), Cu(II), Cd(II) and Ni(II), which demonstrated that Cr(VI)-IIP could be applied in complex aqueous environments to achieve efficient separation of Cr(VI) while enabling the separation of different valence states of elemental Cr.…”
Section: Polymeric Materials For Solid-phase Extractionmentioning
confidence: 99%
“…Under the optimal conditions, Cr(III) was absorbed quantitatively, but Cr(VI) was not retained. A novel Cr(VI)-IIP was synthesized on the surface of mesoporous silicon (SBA-15) using MAA and 4-VP as bifunctional monomers and Cr(VI) anion as template ion by surface thermal initiation imprinting technique [ 127 ]. Cr(VI)-IIP prepared possesses a strong selective adsorption ability for Cr(VI) in the presence of competing ions such as Cr(III), Cu(II), Cd(II) and Ni(II), which demonstrated that Cr(VI)-IIP could be applied in complex aqueous environments to achieve efficient separation of Cr(VI) while enabling the separation of different valence states of elemental Cr.…”
Section: Polymeric Materials For Solid-phase Extractionmentioning
confidence: 99%